Applying image processing methods to study hydrodynamic characteristics in a rectangular spouted bed. (12th October 2018) - Yang, Jingsi; Breault, Ronald W.; Rowan, Steven L.
Graphical abstract: Highlights: The bed expansion ratio (H/H0 ) is obtained by image analysis and defined algorithm. The jet (Hj ) and fountain (Hf ) heights are determined by image contour detection. The H/H0 reaches a maximum value of 1.4 at the onset of the external spouting. The profiles of Hj and Hf vs. Ug verifies the feasibility of the image methods. The flow regime determination proves that the image methods is effective and useful. Abstract: This paper presents systematic image processing methods for investigating hydrodynamic characteristics in a rectangular spouted bed (30.2 mm × 101.6 mm). The objective is to provide a non-intrusive technique to determine the bed expansion ratio, the jet height and the fountain height due to their significant influence on the hydrodynamics of the entire bed. A high-speed video camera is used in the experiment with Geldart D particles as the bed material. After the image acquisition, image denoising, thresholding, logical and mask operations are applied correspondingly for the boundary discrimination, based on which an algorithm has been developed to determine the bed height successfully. With the discriminated boundary, morphological operations viz. erosion and dilation have been used to accurately determine the jet height and the fountain height. The feasibility of the technique is proven through profiles of bed expansion ratio, jet height and fountain height under three initial bed heights (0.0762 m, 0.102 m, and 0.127 m) for two different nozzle sizes (0.0096 m and 0.0127 m). Depending on the determination of the hydrodynamic characteristics, different flow regimes can be distinguished comprehensively through profiles of the bed expansion ratio and bed pressure drop in combination with the standard deviation of jet/fountain height. The proposed flow regime discrimination verifies the feasibility and effectiveness of the image processing methods in assessing the solids behavior in the spouted beds. Results about the variation of the jet height and the fountain height under current operating conditions as determined by the new technique are also discussed. This work has been selected by the Editors as a Featured Cover Article for this issue.